(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of treatment using electroacupuncture, hydroacupuncture combined with acupressure massage to restore motor function in children with sequelae of viral encephalitis at National Hospital of Acupuncture, in 2022-2023. Subjects and methods: Clinical intervention with control on 130 pediatric patients with sequelae of viral encephalitis at National Hospital of Acupuncture from January 2022 to December 2023. Results: The study group had 80% improvement rate in spasticity; 76.92% improvement rate in motor paralysis; and 83.09% improvement rate in gross motor function. The effectiveness of motor rehabilitation treatment in the study group was 1.46-1.52 times higher than that of the control group, with statistical significance at p < 0.05. Conclusion: The application of electroacupuncture, hydroacupuncture Cerebrolysin and Vincozyn plus combined with acupressure massage increases the effectiveness of motor rehabilitation treatment in children with sequences of viral encephalitis